2001
DOI: 10.1002/1521-3749(200108)627:8<1782::aid-zaac1782>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Kristallstruktur von KTeOF3

Abstract: Ad memoriam Egon WibergInhaltsu È bersicht. KTeOF 3 wurde durch Festko È rpersynthese aus a È quimolaren Mengen an KF, TeO 2 und KTeF 5 dargestellt und seine Kristallstruktur mittels Ro È ntgeneinkristallstrukturanalyse aufgekla Èrt (P4 2 /n, a = 1007,96(3), c = 789,58(3) pm, Z = 8, R 1 = 0,0311). Als charakteristisches Strukturmerkmal liegen bisher unbekannte dimere Anionen Te 2 O 2 F 6 2± vor, die aus zwei kantenverknu È pften pseudooktaedrischen Einheiten aufgebaut sind. IR-und Raman-Daten werden mitgeteilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These directional repulsion effects by lone valence electron pairs and p bonds in trigonal bipyramidal molecules have been discussed by us in detail previously [61]. A discussion of trends within the SOF 3 À , SeOF 3 À , and TeOF 3 À series is not warranted at this point because for SOF 3 À only a low-level calculated structure is available, and for TeOF 3 À the experimental structure contains oxygen-bridged dimeric anions [24] which are also present in the complex salt [C 5 H 6 N] 2 [TeF 5 ][Te 2 O 2 F 6 ] 0.5 [25]. Therefore, the crystal structure of SeOF 3 À represents the first experimentally well-determined molecular structure of a monomeric trifluoro-chalcogenite anion.…”
Section: àmentioning
confidence: 99%
“…These directional repulsion effects by lone valence electron pairs and p bonds in trigonal bipyramidal molecules have been discussed by us in detail previously [61]. A discussion of trends within the SOF 3 À , SeOF 3 À , and TeOF 3 À series is not warranted at this point because for SOF 3 À only a low-level calculated structure is available, and for TeOF 3 À the experimental structure contains oxygen-bridged dimeric anions [24] which are also present in the complex salt [C 5 H 6 N] 2 [TeF 5 ][Te 2 O 2 F 6 ] 0.5 [25]. Therefore, the crystal structure of SeOF 3 À represents the first experimentally well-determined molecular structure of a monomeric trifluoro-chalcogenite anion.…”
Section: àmentioning
confidence: 99%
“…Hence, it has to be concluded that the crystal structure, in fact, contains the [Te 2 O 2 F 6 ] 2À anion (Fig. 1 (Kessler & Jansen, 2001). The formation of the crystals described here can be explained by slow partial hydrolysis of two molecules of [ (Mahjoub et al, 1992), the [TeF 5 ] À anions participate in intermolecular interactions, with a Te2Á Á ÁF8 ii distance of 3.151 (2) Å [symmetry code: (ii) x, 1.5 À y, 1 2 + z].…”
Section: Commentmentioning
confidence: 83%
“…During our recent investigations (Klapö tke et al, 2003) on binary covalent tellurium azides, a stabilization of the tetraazide Te(N 3 ) 4 as a pyridine adduct was desirable. Adducts of TeF 4 with Lewis bases L have been reported (L = Me 3 N, dioxane, bipyridine and tetramethylethylenediamine), but apart from elemental analysis, no analytical information has been obtained (Greenwood et al, 1966).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nice illustration of how an inorganic element can dictate molecular structure, bis­(pentafluorophenyl)tellurium oxide, [(F 5 C 6 ) 2 Te­(μ-O)] 2 ( 948 ), is a centrosymmetric dimer with a planar Te 2 O 2 ring, while its selenium congener is a weakly associated hexamer, [(F 5 C 6 ) 2 SeO] 6 ( 949 ), with long Se---O and Se---Se bonds; both species were formed via the oxidation of the Se­(II) and Te­(II) precursors, Ch­(C 6 F 5 ) 2 (Ch = Se and Te), with m -chloroperbenzoic acid in chloroform . Structurally related tellurium oxide heterocycles characterized in the literature include a polymorph of 948 , [(2,4,6-Ph 3 C 6 H 2 )­Te­(μ-O)­X] 2 (X = Br and I; 950 and 951 ), the siloxy-capped tellurium­(VI) oxide [(Me 3 SiO) 4 Te­(μ-O)] 2 ( 952 ), [(2,6-(MeO) 2 C 6 H 3 )­Te­(μ-O)­OMe] 2 ( 953 ), salts of the dianion [F 3 Te­(μ-O)­TeF 3 ] 2– ( 954 ), and the ureatotellurium oxide [( t BuNC­(O)­N t Bu)­Te­(μ-O)] 2 ( 955 ) …”
Section: Inorganic Rings Derived From Group 12–17 Elementsmentioning
confidence: 99%